Induction Motor Characteristics Study using Laboratory Instrument Engineering Workbench - E. Ramprasath; P. Manojkumar; P. Veena (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Induction motor characteristics are complex to study, so in order to simplify its complexity modelling of induction motor will be useful. Proposed paper dealt with the simulation of induction motor based on the mathematical expression using the graphical user interface software. Laboratory Virtual Instrument Engineering Workbench (LabVIEW) software is used for modelling the induction motor and helps in analyzing the performance characteristics of a machine. After the invention of special electrical machine the research in induction motor starts to decreases but it is the widely used motor in industries. The study about induction motor characteristics became complex after the incorporation of power electronic switches such as thyristor, diodes, GTO, and MOSFET. In duction motor characteristics can be studied and modelled with the help of numerous software’s such as Finite Element Analysis and Laboratory Virtual Instrument Engineering Workbench. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8004